The Moral Cultivation Mechanism in International Student Management from the Perspective of Cultural Identity - Xiang, Shiqi (International Journal of Social Sciences and Public Administration, 2026)
With the continuous development of internationalization in universities, more and more foreign students are coming to China to study and playing an increasingly important role in their university life. How to provide correct moral education and cultivate good habits for international students is also an important component of ideological and political education for college students. The article focuses on cultural identity and systematically elaborates on the role of moral education in the management of international students, as well as the existing problems and countermeasures.The author proposes that cultural identity is the process by which people recognize, accept, and internalize a certain culture; There is an inherent consistency and unity between it and moral development, which has a positive impact on the formation of values, the selection of norms, and self positioning. In reality, the moral development of international students from various countries has encountered problems such as cultural differences, discomfort in educational methods, difficulties in adapting to schools, and cultural barriers in management mechanisms. Therefore, how to solve the above problems has become the focus of our thinking. Therefore, the author believes that we should carry out virtue education work from the perspective of enhancing cultural identity. Specifically, we can start from the following aspects: attaching importance to value discussions based on cultural understanding; Emphasize cross-cultural curriculum and activity design; Emphasize the reconstruction of school culture construction; Emphasize the infiltration of virtue education in management and service. Its purpose is to break through the one-dimensional constraints of behavioral training, allowing international students to naturally integrate value concepts and internalize them into virtues and qualities in the process of cross-cultural adaptation based on multicultural cognition, tolerance, and identification, in order to better assist their comprehensive growth, and provide ideas and solutions for universities to enhance the effectiveness of international education.